Study on Water-Induced Ultra-Weak Luminescence Value of Wheat Kernels - Yitao Liang; Rui Pang; Wang Feng; Hu Yuankun (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
The wheat kernels were processed by moistened in water. The spontaneous and water-induced luminescence data (photon counts) were noted with an ultra-weak luminescence (UWL) detector. The following was the features of the data analyzed by the statistical parameters of the spontaneous luminescence and the fitting curves of the water-induced luminescence. The results show that the UWL intensity rises with the moistened time prolonged. It is concluded that the intensity depends on the moistened time mainly. If the moistened kernels owned a more porous structure, in the initial phase of imbibition, a higher UWL emission would be noted. Consequently, the further quantitative research of the relevant could lead a novel testing method about the wheat’s activity and quality. DOI: http://dx.doi.org/10.11591/telkomnika.v11i9.3150